Record Tracks of Islamic Accounting Thought according to Sofyan Safri Harahap and Iwan Triwuyono - Ismail Ismail; Saparuddin Siregar; Azhari Akmal Tarigan (Jurnal Ilmiah Ekonomi Islam, 2022)
In life, muamalah activities are an interaction in maintaining the teachings contained in the Qur'an, Islam always teaches how to be responsible and how to do justice in muamalah, especially in recording and managing finances and assets. This study seeks to explore how the thoughts of two Indonesian accounting figures, Sofyan Safri Harahap and Iwan Triwuyono, in applying records that are in accordance with Islamic principles and teachings by referring to several articles published on Google Schoolar. The results of this study reveal that there are some similarities in perceptions and thoughts in the philosophical basis of thinking about Islamic accounting, especially on the basis of the philosophy of monotheism then Islamic accounting plays an important role in being responsible and fostering an attitude of justice in recording, especially in Islamic financial institutions that are widely operating today.